2016
DOI: 10.18542/rebac.v10i2.3481
|View full text |Cite
|
Sign up to set email alerts
|

Discriminação Simples Entre Estímulos Visuais E Reversões Sucessivas De Discriminação Em Abelhas (Melipona Quadrifasciata)

Abstract: RESUMOCom exceção dos estudos pioneiros de Isaías Pessotti sobre aprendizagem discriminativa em abelhas, outros trabalhos frequentemente empregaram procedimentos com características que dificultam o controle experimental rigoroso e uma interpretação segura dos dados (por exemplo, definição ambígua da resposta, treino simultâneo de vários sujeitos e análise de dados agrupados). Além disso, poucos estudos investigaram a aprendizagem discriminativa em outras espécies além de Apis mellifera e Bombus terrestris. O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Research with invertebrates has shown that bees (mostly Apis , Bombus , and Melipona ) can respond to colors, geometric patterns, scents and human faces on simple and conditional discriminations; they can reverse simple discriminations; and they can attend to a particular feature of visual stimuli (for a review, see Moreno, Rocca, & de Souza, ). The discriminative capabilities of old‐world Apis mellifera are probably the most extensively described in the literature and include complex learning of ‘sameness' and ‘difference’ concepts (Giurfa, Zhang, Jenett, Menzel, & Srinivasan, ).…”
mentioning
confidence: 99%
“…Research with invertebrates has shown that bees (mostly Apis , Bombus , and Melipona ) can respond to colors, geometric patterns, scents and human faces on simple and conditional discriminations; they can reverse simple discriminations; and they can attend to a particular feature of visual stimuli (for a review, see Moreno, Rocca, & de Souza, ). The discriminative capabilities of old‐world Apis mellifera are probably the most extensively described in the literature and include complex learning of ‘sameness' and ‘difference’ concepts (Giurfa, Zhang, Jenett, Menzel, & Srinivasan, ).…”
mentioning
confidence: 99%